2020
DOI: 10.3390/cancers12092625
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study Using Plasma Apolipoprotein A2-Isoforms to Screen for High-Risk Status of Pancreatic Cancer

Abstract: Apolipoprotein A2-ATQ/AT (apoA2-ATQ/AT) has been identified as a minimally invasive biomarker for detecting pancreatic cancer (PC) and high-risk (HR) individuals for PC. To establish an efficient enrichment strategy for HR, we carried out a plasma apoA2-ATQ/AT level-based prospective screening study among the general population. The subjects for the screening study were recruited at six medical check-up facilities in Japan between October 2015 and January 2017. We evaluated the positive predictive value (PPV) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…Then, GO and REACTOME pathway analyses were used to investigate the interactions of these DEGs. Increasing evidence shows that LAPTM4B [52], CEACAM6 [53], SERPINE2 [54] and VNN1 [55], SPHK1 [56], HRG (histidine rich glycoprotein) [57], VEGFC (vascular endothelial growth factor C) [58], ANXA3 [59], APOA2 [60], LCN2 [61], TIMP1 [62], CD63 [63], CD151 [64], MAL2 [65], ARNTL2 [66], PKD2 [67], E2F1 [68], MMP1 [69], CCR7 [70], NOTCH2 [71], BTLA (B and T lymphocyte associated) [72], TFRC (transferrin receptor) [73], CD4 [74], ATM (ATM serine/threonine kinase) [75], LEF1 [76], CSF1R [77], CTSB (cathepsin B) [78], DUSP2 [79] and NR4A1 [80] are closely associated with progression of PDAC. PTGER3 [81] and MAGI2 [82] are linked with angiogenesis, chemoresistance, cell proliferation and migration in ovary cancer, but these genes might be liable for growth PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…Then, GO and REACTOME pathway analyses were used to investigate the interactions of these DEGs. Increasing evidence shows that LAPTM4B [52], CEACAM6 [53], SERPINE2 [54] and VNN1 [55], SPHK1 [56], HRG (histidine rich glycoprotein) [57], VEGFC (vascular endothelial growth factor C) [58], ANXA3 [59], APOA2 [60], LCN2 [61], TIMP1 [62], CD63 [63], CD151 [64], MAL2 [65], ARNTL2 [66], PKD2 [67], E2F1 [68], MMP1 [69], CCR7 [70], NOTCH2 [71], BTLA (B and T lymphocyte associated) [72], TFRC (transferrin receptor) [73], CD4 [74], ATM (ATM serine/threonine kinase) [75], LEF1 [76], CSF1R [77], CTSB (cathepsin B) [78], DUSP2 [79] and NR4A1 [80] are closely associated with progression of PDAC. PTGER3 [81] and MAGI2 [82] are linked with angiogenesis, chemoresistance, cell proliferation and migration in ovary cancer, but these genes might be liable for growth PDAC.…”
Section: Discussionmentioning
confidence: 99%
“…The comparison of background characteristics between apoA2-ATQ/AT-positive and -negative groups in the experimental screening study showed that age (years) [odds ratio (OR) 1.37, 95% CI 1.01–1.85], white blood cells (OR 1.32, 95% CI 1.11–1.56), total cholesterol (OR 0.94, 95% CI 0.92–0.97), low-density lipoprotein (OR 1.05, 95% CI 1.01–1.08), and pancreatic lesions detected by ultrasonography (%) (OR 3.04, 95% CI 1.01–9.14) remained significant on the multivariate logistic regression analyses (Table 1 ) [ 22 ]. Interestingly, the most strongly associated factor in the comparison of background characteristics was pancreatic lesions detected by ultrasonography.…”
Section: Experimental Screening For Pancreatic Cancer Using the Apoa2...mentioning
confidence: 99%
“…
Figure 6. Flow diagram of the experimental screening of pancreatic cancer using the apoA2-i blood test in the Kobe Cancer Screening Network [ 22 ]. CECT, contrast-enhanced computed tomography; MRCP, magnetic resonance cholangiopancreatography; EUS, endoscopic ultrasonography; PDAC, pancreatic adenocarcinoma cancer; IPMN, intraductal papillary mucinous neoplasms; CP, chronic pancreatitis; NET, pancreatic neuroendocrine tumors; AIP, autoimmune pancreatitis.
…”
Section: Future Perspectivementioning
confidence: 99%
“…APOA2 was prospectively evaluated in 2019 where it was identified to be useful when utilized in combination with CA19-9 to improve detection of PC up to 18 mo prior to diagnosis and was suggested to be a useful first measure of PC detection prior to imaging[ 207 ]. This was built upon in 2020, where APOA2-ATQ/AT was implemented in a screening cohort in which an elevated level resulted in a PPV of 33.3% for the diagnosis of PC[ 208 ].…”
Section: Serological Biomarkers Of Pcmentioning
confidence: 99%